Identification and Characterization of Integron-Mediated Antibiotic Resistance among Shiga Toxin-Producing Escherichia coli Isolates - Zhao, Shaohua (American Society for Microbiology, 2001)
A total of 50 isolates of Shiga toxin-producing Escherichia coli (STEC), including 29 O157:H7 and 21 non-O157 STEC strains, were analyzed for antimicrobial susceptibilities and the presence of class 1 integrons. Seventy-eight (n = 39) percent of the isolates exhibited resistance to two or more antimicrobial classes. Multiple resistance to streptomycin, sulfamethoxazole, and tetracycline was most often observed. Class 1 integrons were identified among nine STEC isolates, including serotypes O157:H7, O111:H11, O111:H8, O111:NM, O103:H2, O45:H2, O26:H11, and O5:NM. The majority of the amplified integron fragments were 1 kb in size with the exception of one E. coli O111:H8 isolate which possessed a 2-kb amplicon. DNA sequence analysis revealed that the integrons identified within the O111:H11, O111:NM, O45:H2, and O26:H11 isolates contained the aadA gene encoding resistance to streptomycin and spectinomycin. Integrons identified among the O157:H7 and O103:H2 isolates also possessed a similar aadA gene. However, DNA sequencing revealed only 86 and 88% homology, respectively. The 2-kb integron of the E. coli O111:H8 isolate contained three genes, dfrXII, aadA2, and a gene of unknown function, orfF, which were 86, 100, and 100% homologous, respectively, to previously reported gene cassettes identified in integrons found in Citrobacter freundii and Klebsiella pneumoniae. Furthermore, integrons identified among the O157:H7 and O111:NM strains were transferable via conjugation to another strain of E. coli O157:H7 and to several strains of Hafnia alvei. To our knowledge, this is the first report of integrons and antibiotic resistance gene cassettes in STEC, in particular E. coli O157:H7.